World Wide Web of Exploitations – the Case of Peacetime Cyber Espionage Operations Under International Law:: Towards a Contextual Approach - Kilovaty, Ido (Science and Technology Law Review, 2017)
The emergence of cyber espionage, as well as the ability to leak gathered sensitive information, has exacerbated the complexity of determining the legality of espionage under international law. Cyber espionage, just like other cyber operations, offers a highly sophisticated, relatively inexpensive, and accessible medium to achieve certain informational, political, and operational goals. The indeterminacy of cyber espionage in international law has given rise to various arguments as to which international norms and principles are applicable to cyber espionage. Divergent positions, however, focus only on certain aspects of cyber espionage. For this reason, the scope of legal treatment of cyber espionage is limited and lacks context. The purpose of this article is to reject this dichotomous approach and propose a more nuanced framework for addressing cyber espionage in international law. Cyber operations should be analyzed on a continuum that triggers different norms depending on the context and consequences. The contextual approach focuses on the effects of a cyber operation and the context in which it occurs to determine the relevant set of norms applicable to it.